2018
DOI: 10.1029/2018jb016209
|View full text |Cite
|
Sign up to set email alerts
|

Relative Paleointensity and Inclination Anomaly Over the Last 8 Myr Obtained From the Integrated Ocean Drilling Program Site U1335 Sediments in the Eastern Equatorial Pacific

Abstract: For understanding the fundamentals of the geodynamo such as the relation between paleointensity and polarity length and time‐averaged field (TAF) structure, continuous records of relative paleointensity (RPI) and inclination anomaly (ΔI) are desired; however, available records older than ~3 Ma are still very limited in time and space. We conducted a paleomagnetic study of the Integrated Ocean Drilling Program Site U1335 sediments in the eastern equatorial Pacific to obtain continuous RPI and ΔI records since ~… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 68 publications
(128 reference statements)
1
36
0
Order By: Relevance
“…Therefore, the correlation between LI ET AL. (Yamazaki & Yamamoto, 2018). our low anomalies and some excursions may indicate that the geomagnetic field intensity was low before and after these excursions over a longer scale.…”
Section: Statistical Analysis Of the Ages Of Tiny Wigglesmentioning
confidence: 83%
See 3 more Smart Citations
“…Therefore, the correlation between LI ET AL. (Yamazaki & Yamamoto, 2018). our low anomalies and some excursions may indicate that the geomagnetic field intensity was low before and after these excursions over a longer scale.…”
Section: Statistical Analysis Of the Ages Of Tiny Wigglesmentioning
confidence: 83%
“…At present, the available relatively long, continuous paleointensity records for the past 11 Myr include marine magnetic anomaly records that span the past 5 Myr (Li et al, 2018) and marine sedimentary records for the past ∼8 Myr (Yamazaki & Yamamoto, 2018). Li et al (2018) generated a composite record of magnetic anomaly profiles from the South Atlantic, verified by those from Central Indian, East Pacific and Pacific-Antarctic ridges (Pouliquen et al, 2001) and RPI data of VM93 and PISO-1500 (Channell et al, 2009;Valet & Meynadier, 1993), and identified 14 additional age calibration points (Figure 3).…”
Section: Correlations With Other Recordsmentioning
confidence: 99%
See 2 more Smart Citations
“…1994, Yamazaki et al, 2008) but reaching far back in time, e.g. back to 10 Ma (Yamazaki & Yamamoto, 2018), with sedimentation rates of just some 1 to 2 cm ka -1 . On the other hand, sites closer to the shore such as ODP Site 1233 in the SE Pacific, offshore Chile, can reach sedimentation rates as high as ~175 cm ka -1 (Lund et al, 2006), providing an extremely high-resolution paleomagnetic record, but only for the past about 70 ka.…”
Section: Accepted Articlementioning
confidence: 99%